2023
DOI: 10.1039/d2ra07247e
|View full text |Cite
|
Sign up to set email alerts
|

Novel hybrids of thiazolidinedione-1,3,4-oxadiazole derivatives: synthesis, molecular docking, MD simulations, ADMET study,in vitro, andin vivoanti-diabetic assessment

Abstract: As compared to standard medicinal compounds, hybrid molecules that contain multiple biologically active functional groups have greater affinity and efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
(40 reference statements)
1
3
0
Order By: Relevance
“…However, it should be noted that the in vitro results showed higher α-glucosidase inhibitory activity compared with the in vivo antidiabetic effect. This finding is consistent with the results of other studies where compounds or extracts with high activity in in vitro assays showed lower activity in in vivo studies, possibly owing to differences in their absorption, distribution and metabolism, as well as the complex pathophysiology of DM (Kabach et al, 2003;Oboh et al, 2019;Srinivasa et al, 2023).…”
Section: Discussionsupporting
confidence: 92%
“…However, it should be noted that the in vitro results showed higher α-glucosidase inhibitory activity compared with the in vivo antidiabetic effect. This finding is consistent with the results of other studies where compounds or extracts with high activity in in vitro assays showed lower activity in in vivo studies, possibly owing to differences in their absorption, distribution and metabolism, as well as the complex pathophysiology of DM (Kabach et al, 2003;Oboh et al, 2019;Srinivasa et al, 2023).…”
Section: Discussionsupporting
confidence: 92%
“…1,3,4‐Oxadiazole clubbed thiazolidinediones 46 a – j were prepared by Srinivasa and coauthors [103] and evaluated for their inhibitory potential against α‐amylase and α‐glucosidase enzymes. Bioassay outcomes revealed that compounds 46 a , 46 b , and 46 j exhibited higher inhibition with IC 50 values ranging from 18.42‐22.60 (α‐amylase) and 17.21–22.25 (α‐glucosidase) than used standard, Acarbose (IC 50 =24.35 and 23.73 μM, respectively).…”
Section: Thiazolidinone Based α‐Amylase Inhibitorsmentioning
confidence: 99%
“…(Figure 1). [32][33][34][35][36] Among them, succinimide-thiazolidinedione [37] and thiazolidinedione-1,3,4-oxadiazole showed anti-diabetic effects, [38] thiazolidinedione-oxoindoline [39] and thiazolidinedione-indole hybrids [40] showed anticancer and 1,3,4-thiadiazole-thiazolidinedione hybrids [41] demonstrated significant anti-inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%